MODEL PERENCANAAN BISNIS BERBASIS NILAI-NILAI ISLAM DALAM MENDORONG KEBERLANJUTAN DAN DAYA SAING USAHA DI ERA DIGITAL - Khusnul Mazidah; Muhammad Sidiq Purnomo (Jurnal Manajemen Pendidikan, 2026)
The rapid advancement of digital technology requires business planning models that integrate strategic management with ethical values to achieve sustainable competitiveness. This study aims to develop an Islamic values-based business planning model by integrating Islamic principles, modern management, and digital technology. A qualitative approach with a library research design was employed. Data were collected through documentation of indexed journal articles, academic books, and other relevant scientific publications, and analyzed using content analysis through data reduction, data display, and interpretative conclusion drawing. The findings reveal that Islamic values, including tauhid, amanah, honesty, justice, and halal principles, can be systematically integrated into all components of business planning, from vision and mission formulation to marketing, financial, and operational strategies. The study proposes an input–process–output–outcome business planning model that combines Islamic values, strategic management, and digital technology to strengthen business sustainability and competitive advantage. The novelty of this study lies in transforming Islamic values into practical strategic elements within business planning, providing a comprehensive framework for business development in the digital era.